2020
DOI: 10.1177/0272431620931191
|View full text |Cite
|
Sign up to set email alerts
|

Peer Victimization and Depressive Symptoms During Adolescence: Examining the Roles of Social Support and Internalizing Coping

Abstract: The purpose of this study was to examine how two coping strategies together moderate the relationship between peer victimization and adjustment among young adolescents. Sixth-grade adolescents from California, Oregon, and Wisconsin ( N = 1,058) self-reported peer victimization, depressive symptoms, and their utilization of social support seeking and internalizing coping. A regression analysis showed a significant three-way interaction between peer victimization, internalizing coping, and social support seeking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…As we all know, peer relations are vitally important for adolescence, and a good peer relationship can buffer an adolescent from adverse effects ( Hoorn et al, 2016 ). In contrast, peer victimization can seriously endanger the physical and mental health of an adolescent ( Farrell and Vaillancourt, 2019 ; Spiekerman et al, 2020 ). Previous studies have demonstrated that peer victimization is closely related to adolescent POGU ( Su et al, 2018 ; Wang et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%
“…As we all know, peer relations are vitally important for adolescence, and a good peer relationship can buffer an adolescent from adverse effects ( Hoorn et al, 2016 ). In contrast, peer victimization can seriously endanger the physical and mental health of an adolescent ( Farrell and Vaillancourt, 2019 ; Spiekerman et al, 2020 ). Previous studies have demonstrated that peer victimization is closely related to adolescent POGU ( Su et al, 2018 ; Wang et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have documented the pernicious effects of peer victimization on mental health, as well as the mitigating role of peer social support (Cooley et al, 2015; Fox & Boulton, 2006; Spiekerman et al, 2021). From a coping perspective, peer support may reduce victimization by promoting greater perceived control in managing stressful peer situations (Cicognani, 2011) and reducing sensitivity to rejection (Stroud et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…By asking for less help, students would have less available social support. Social support is essential for reducing the negative psychological consequences of peer victimization [51,57,[66][67][68], but many victimized students may have difficulties in accessing it. Moreover, as no significant differences were found in the other coping strategies, classmates may differently perceive the same coping strategies depending on whether it was carried out by a victimized or non-victimized student.…”
Section: Discussionmentioning
confidence: 99%